Islamic religious education learning innovations in strengthening character education in the Industrial Revolution Era 4.0 - Harimawan Harimawan; Arif Budi Raharjo; Eko Harianto (DWIJA CENDEKIA: Jurnal Riset Pedagogik, 2024)
This research is based on the role of Islamic Religious Education (PAI) subjects in strengthening student character in the era of Industrial Revolution 4.0 at SMK Muhammadiyah 1 Bantul. In connection with this, this research aims to determine Islamic religious education (PAI) learning innovations in strengthening the character of the Industrial Revolution 4.0 at SMK Muhammadiyah 1 Bantul. This research uses qualitative research methods, which are delivered descriptively. Sources of information in this research include school principals, teachers, education staff, and students who participate in learning activities in class XI of the Automotive Light Vehicle Engineering Skills Program (TKRO) at SMK Muhammadiyah 1 Bantul. The primary data source is in the form of the words and actions of the subject, which is the focus of the research; the rest is in the form of additional data such as documents, photos, and others. This research concluded that the "Kaizen" method, which originates from Japanese, the Japanese concept of Continuous Incremental Improvement, can strengthen character education and become a PAI learning innovation in the era of the Industrial Revolution 4.0. The "Kaizen" method includes five stages with the prefix "S": Seiri, Seiton, Seiso, Seiketsu, and Shitsuke.